Об одной проблеме Стефана - Шевченко, А.И.; Миненко, А.С. (Видавничий дім "Академперіодика" НАН України, 2008)
By using the variational method, we study a nonlinear thermophysical problem with a free boundary. It is proved that an approximate solution based on the Ritz method tends to the exact one in a certain metric.